Economic Indigenization and Islamic Economics: Remarks on Comparative and Foundational Approaches - Masoud Derakhshan (فصلنامه پژوهش‌های اقتصادی ایران, 2012)
We first define and briefly examine the “imitative” and “indigenal” approaches in conventional economic theories from an Islamic Economic perspective. We then review briefly the concepts of “indigenous” and “indigenization” in the humanities and social sciences from the points of view expressed by Imam Khomeini (ره) and the Supreme Leader. We have subdivided the “indigenal approach” into “comparative” and “foundational” approaches. It is shown that in the comparative approach, a critical analysis of the underlying assumptions in economic theories, and specifying the shortcomings of the logic of abstraction employed in economic theorization particularly in identification of economic players and their status in conventional economic theories, can be productive. However, this approach suffers from the lack of adequate potentialities for successful theorization in Islamic Economics, hence cannot be used as a basis for economic policy formations. The paper concludes by proposing the foundational approach as the only solution to indigenization of economics as well as the necessary condition in building Islamic-Iranian model of economic progress.